Bibliometric modelling and policy making - Smith, Kerry; Marinova, D. (Modelling and Simulation Society of Australia and New Zealand Inc., 2003)
Bibliometric methods for analysing and describing research output have been in existence and usage for over half a century. This has been supported internationally by the establishment and operations of organisations such as the Institute for Scientific Information (ISI) and the continual release and calculations of journal lists, bibliometric indicators and rankings. More recently bibliometric analyses have responded to the changes posed by the growing field of Internet publishing by incorporating some electronic versions of journals. Policy makers in Australia have been relying on such bibliometric information and analyses in making funding decisions and encouraging the development of research potential and strengths. This raises a number of concerns. Does bibliometric modelling of research productivity reflect the real impact research has for Australia's future? Is the electronic word in all its varieties overpowering the printed word? Is the grey literature as important as the officially recognised prestigious publications? Are the expectations policy makers, policy executives and managers draw from bibliometric modelling justified? The paper attempts to provide some answers to these questions based on a study of three Australian research centres in the field of the geosciences. The analysis reveals a number of anomalies in the generalisations made when ISI models are used for policy decisions.